The Influence of Financial Literacy and Lifestyle on Student Consumptive Behavior (Study at the Faculty of Economics and Business, UKI Paulus Makassar) - Halik, Johannes Baptista; Mongan, Benyamin; Kamban, Stevani Tandi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This research aims to analyze the influence of financial literacy and lifestyle on the consumptive behavior of students at the Faculty of Economics and Business, Paulus Indonesian Christian University, Makassar. The research method used is quantitative, namely systematic scientific research on relationships or influences obtained using statistical models, involving 88 respondents from the active student population. The technique used in this sampling is a simple random sampling technique. Data is collected through questionnaires that measure financial literacy, lifestyle and consumer behavior. The results of analysis using Partial Least Squares-Structural Equation Modeling (PLS-SEM) show that financial literacy has no significant effect on consumptive behavior, while lifestyle has a positive and significant effect. These findings indicate that even though students have good financial literacy, lifestyle factors that tend to be consumptive are more dominant in influencing their shopping behavior. It is hoped that this research will provide insight into better financial management among students and encourage the importance of financial literacy education.